A69 THE MOLECULAR LANDSCAPE IN ULCERATIVE COLITIS. (1st March 2018) - Madill-Thomsen, K; Jovanovic, V; Venner, J; Famulski, K; Withecomb, S; Parkes, M; Thiesen, A; Fedorak, R; Halloran, P; Halloran, B P
Abstract: Background: Ulcerative colitis (UC) is a chronic, idiopathic inflammatory condition affecting the colonic epithelium, with the inflammasome, T cells, complement activation, and microbiome dysbiosis contributing to pathogenesis. Aims: We applied a previously established method of microarray molecular analysis to a set of 71 UC biopsies (from 61 patients), to elucidate the molecular changes associated with active UC, specifically comparing UC to T-cell mediated rejection (TCMR), as a prototype of a sterile, T-cell mediated disease. Methods: 71 for-cause UC colonic biopsies were collected at the U of A Hospital in Edmonton, AB and Cedars-Sinai Hospital in LA, California. These biopsies were processed using Affymetrix GeneChip microarrays and the data analyzed in R programming language. Gene expression data was displayed using volcano plots (showing the fold change and association between the genes and endoscopic Mayo score) and heatmaps (showing expression of the top 30 genes in a cell panel). We then analyzed overexpression of the top genes using the DAVID tool 1, and compared the results to similar results for top genes overexpressed in TCMR. Results: The volcano plot (Figure 1) showed strong associations between the endoscopic Mayo score and decay accelerating factor (CD55), and moderate associations with calprotectin genes (S100A8/S100A9), with lesser associations for effector T cell transcripts (i.e. CTLA4, interferon gamma (IFNG), and chemokine ligand (CXCL13)), many IFNG inducible transcripts, inflammasome transcripts (CASP1), and toll-like receptors (TLR5). NLRP3 (incriminated in mouse UC models) did not pass the IQR filter and was not significant. Expression of the top genes in a cell panel showed primary expression in monocytes, macrophages, and dendritic cells, with some expression in epithelial and endothelial cells, while minimal expression was found in CD4/CD8 T cells, or in NK cells. Pathway analysis showed major differences between pathway terms. Conclusions: Our findings show that while transcripts associated with cognate T cell inflammatory processes (TCMR) are expressed in UC, there are substantial differences between the pathogenesis of a pure T cell-mediated disease and UC. In our cohort, the top genes associated with the endoscopic Mayo score in UC were not those associated with effector T cells: T cell-associated transcripts were only moderately associated with the Mayo score, and pathway analysis showed significant differences between TCMR and UC, which is much more an inflammatory environment with strong associations to CD55. This suggests that cognate T cell recognition is present in UC but supplemented by a second source of inflammation. REFERENCES: 1. Huang et al. Systematic and integrative analysis of large gene lists using DAVID bioinformatics resources. Nature Protocols (2009). Funding Agencies: None